Physicochemical and Toxicological Properties of Particles Emitted from Scalmalloy During the LPBF Process - Nikoletta Sargioti; Leonidas Karavias; Leonidas Gargalis; Anna Karatza; Elias P. Koumoulos; Evangelia K. Karaxi (Toxics)
This study investigates the physicochemical and toxicological properties of Scalmalloy powder emissions generated during Laser Powder Bed Fusion (LPBF), focusing on the impact of particle morphology, oxidation, and size distribution on biological responses. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analyses revealed significant variations in particle characteristics, with the highest oxidation levels and irregular morphologies observed in exhaust-derived powders. In vitro cytotoxicity evaluations using A549 lung epithelial cells showed significant reductions in cell viability (~60 to 69%) and increased oxidative stress (p < 0.05) upon exposure to virgin sieved (<20 µm) and exhaust powder samples. Conversely, samples from the build plate, overflow, and dispenser exhibited high cell viability (>85%). Indirect exposure through media incubation resulted in minimal cytotoxicity, suggesting that metal dissolution plays a limited role in toxicity under the studied conditions. The findings highlight the influence of particle morphology and oxidation on cytotoxic responses and underscore the need for controlled powder handling to mitigate occupational exposure risks in LPBF environments.